2006
DOI: 10.5713/ajas.2006.335
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mercury in the Etiology of Sperm Dysfunction in Holstein Bulls

Abstract: A large number of toxicological substances and pharmacological and physical agents can cause reproductive intervention at the cellular and molecular level. The present study was designed to assess the effect of mercury (HgCl 2 ) at 50 to 550 µM concentration ranges, in vitro, on the sperm membrane and DNA integrity, viability, and acrosomal status of normal bull spermatozoa. The samples were processed for sperm analyses using semen-diluting fluid (PBS, pH 7.2). We recorded a sharp increase in the lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…We observed that a concentration of 50 lg ⁄ ml of cadmium significantly decreased spermatozoa motility and is in agreement to the earlier report in cattle (Massanyi et al 1996). In cattle, cadmium at various concentrations ranging from 20 lM (Leoni et al 2002) to 250-300 lM (Arabi 2006;Arabi and Mohammadpour 2006) significantly affected bull sperm motility. This might be owing to differences in sperm processing, incubation time and the method used for examining viability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that a concentration of 50 lg ⁄ ml of cadmium significantly decreased spermatozoa motility and is in agreement to the earlier report in cattle (Massanyi et al 1996). In cattle, cadmium at various concentrations ranging from 20 lM (Leoni et al 2002) to 250-300 lM (Arabi 2006;Arabi and Mohammadpour 2006) significantly affected bull sperm motility. This might be owing to differences in sperm processing, incubation time and the method used for examining viability.…”
Section: Discussionsupporting
confidence: 92%
“…In cattle, cadmium at various concentrations ranging from 20 μ m (Leoni et al. 2002) to 250–300 μ m (Arabi 2006; Arabi and Mohammadpour 2006) significantly affected bull sperm motility. This might be owing to differences in sperm processing, incubation time and the method used for examining viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lead, mercury, cadmium, nickel and arsenic have been reported to adversely affect male fertility including fertilizing competence of spermatozoa 1 . In-vivo toxicological studies have shown that heavy metals have the tendency to accumulate in testis and disrupt endocrine and regenerative capacity of testicular cells 2 .…”
Section: Introductionmentioning
confidence: 99%